Functional role of miR-34a in diabetes and frailty - Mone, Pasquale; de Donato, Antonio; Varzideh, Fahimeh; Kansakar, Urna; Jankauskas, Stanislovas S.; Pansini, Antonella; Santulli, Gaetano (Frontiers in Aging, 2022)
Emerging evidence has shown that microRNAs (miRNAs) play critical role in the pathogenesis of several disorders. In the present minireview, we focus our attention on the functional role of a specific miRNA, namely miR-34a, in the pathophysiology of frailty and diabetes mellitus. Based on the current literature, we speculate that this miRNA may serve as a potential biomarker of frailty in diabetic older adults. Additionally, its actions on oxidative stress might represent a druggable target to obtain new potentials treatments.